Charging process of a partially heated trapezoidal thermal energy storage filled by nano-enhanced PCM using controlable uniform magnetic field. (November 2022) - Izadi, Mohsen; Hajjar, Ahmad; Alshehri, Hashim M.; Sheremet, Mikhail; Galal, Ahmed M.
Abstract: This paper presents a computational analysis of the flow and thermal behaviors of a nano-enhanced Phase Change Material (PCM) exposed to a magnetic field. One of the applications of PCM is to use for thermal charging of heat storage devices, which can be used in renewable energy management. The PCM is placed in a trapezoidal enclosure with a partially heated bottom wall, while the other walls are insulated. The equations governing the flow and heat transfer in the PCM are first defined and converted into the non-dimensional form. The finite element method is then employed to solve these equations. The impacts of various parameters on the PCM melting time and Nusselt number, are studied. In particular, the results showed that raising Rayleigh number enhances PCM melting due to increased buoyancy effects but only for low values of Hartmann number. Increasing the latter decreases the resistive magnetic effects which limits the convective flow and reduces melting. The volume fraction also had a slight impact on the PCM behavior. Raising the fraction improved the thermal conductivity of the working fluid and consequently increased the amount of melted PCM in the cavity. Highlights: Thermal behaviors of a nano-enhanced PCM under a magnetic field. Impact of Ra was dependent on the value of Hartmann number. Raising Ha had a negative effect on PCM melting. Variation of the magnetic field inclination had a slighter effect on the results. Increasing the volume fraction of the nanoparticles lead to a faster melting.